THE IMPLEMENTATION OF ENGLISH SONGS TO INCREASE VOCABULARY RETENTION AMONG STUDENTS WITH ADHD: A CASE STUDY AT CLASS VIII - Icha Fahriza (BRIGHT VISION, 2026)
This study aims to describe and analyze the implementation of using English songs to improve vocabulary retention among students with ADHD characteristics in the eighth grade at a junior high school in North Sumatra. The method used in this study is a qualitative method with a descriptive approach supported by quantitative data in the form of screening results. Based on the screening results using the Conners Rating Scale, out of 300 students, 9 students (3%) were identified as having ADHD characteristics. The subjects of this study were focused on 3 students of Class VIII who have ADHD characteristics and one English teacher as the main informant.The data collection techniques were conducted through ADHD screening, questionnaires, and in-depth interviews. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study show that the use of English songs can improve students’ attention, learning motivation, and help them remember and retain vocabulary for a longer period of time. Songs provide repetition, meaningful context, and an enjoyable learning atmosphere, which support the learning process of students with ADHD Thus, it can be concluded that the implementation of English songs is an effective learning strategy in improving vocabulary retention among students with ADHD characteristics at Class VIII.